2011
DOI: 10.1097/sle.0b013e31822a2373
|View full text |Cite
|
Sign up to set email alerts
|

Relaparoscopy in Minor Bile Leakage After Laparoscopic Cholecystectomy

Abstract: Relaparoscopy is an effective procedure in the management of minor bile leakage after laparoscopic cholecystectomy and can be an alternative approach in selected situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Objectively, they may show evidence of obstructive jaun dice, sepsis, or documented bile leakage. 1,2,5 For patients with bile peritonitis, it is important to implement a rigorous workup, including cholangiography via magnetic resonance cholangiopancreatography (MRCP), percutaneous trans hepatic cholangiography (PTC), or endoscopic retrograde cholangiopancreatography (ERCP). Likewise, control of bilomas or bile peritonitis is imperative.…”
Section: Postoperative Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Objectively, they may show evidence of obstructive jaun dice, sepsis, or documented bile leakage. 1,2,5 For patients with bile peritonitis, it is important to implement a rigorous workup, including cholangiography via magnetic resonance cholangiopancreatography (MRCP), percutaneous trans hepatic cholangiography (PTC), or endoscopic retrograde cholangiopancreatography (ERCP). Likewise, control of bilomas or bile peritonitis is imperative.…”
Section: Postoperative Presentationmentioning
confidence: 99%
“…5,[7][8][9] Returning to the operating room early following surgery allows for the drainage of a biloma or intraabdominal collection, clipping of any acces sory ducts or an insecure cystic duct, inspection of the bili ary anatomy with potential treatment (i.e., releasing a clipped CBD), or placement of a drain to control the leak conservatively. We discuss this topic in further detail below, in the management section.…”
Section: Postoperativementioning
confidence: 99%
See 2 more Smart Citations
“…It usually takes 3‐12 days for the bile leakage to disappear after endoscopic treatment . Some studies have shown that some patients who underwent relaparoscopy selectively had a shorter hospital stay than those who underwent ERCP as the intervention …”
Section: Discussionmentioning
confidence: 99%